2000
DOI: 10.1152/ajpendo.2000.279.6.e1325
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the variability in respiratory exchange ratio at rest and during exercise in trained athletes

Abstract: We examined the variability and determinants of the respiratory exchange ratio (RER) at rest and during exercise in 61 trained cyclists. Fasting (10-12 h) RER was measured at rest and during exercise at 25, 50, and 70% of peak power output (W(peak)), during which blood samples were drawn for [lactate] and [free fatty acid] ([FFA]). Before these measurements, training volume, dietary intake and muscle fiber composition, [substrate], and enzyme activities were determined. There was large interindividual variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
143
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(166 citation statements)
references
References 44 publications
21
143
0
2
Order By: Relevance
“…The intensity at which peak fat oxidation occurs is within the range that can be expected for sedentary subjects 9,18 within L-RER group, whereas for H-RER group the exercise intensity is somewhat low compared with previously reported results. Plasma NEFA was positively correlated to peak fat oxidation in the overweight sedentary men, which is consistent with findings reported by Goedecke et al 10 in lean athletes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The intensity at which peak fat oxidation occurs is within the range that can be expected for sedentary subjects 9,18 within L-RER group, whereas for H-RER group the exercise intensity is somewhat low compared with previously reported results. Plasma NEFA was positively correlated to peak fat oxidation in the overweight sedentary men, which is consistent with findings reported by Goedecke et al 10 in lean athletes.…”
Section: Discussionsupporting
confidence: 92%
“…18,30 Interestingly, peak fat oxidation in subjects having similar VO 2max shows a marked variation in both lean sedentary 9,29 and trained individuals. 10 In this study we show that also in overweight sedentary male subjects major heterogeneity amounting to a twofold difference in peak fat oxidation during exercise is present. The intensity at which peak fat oxidation occurs is within the range that can be expected for sedentary subjects 9,18 within L-RER group, whereas for H-RER group the exercise intensity is somewhat low compared with previously reported results.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous studies have shown that there are large interindividual variations in FA utilization both at rest and during exercise (14,16), and there is evidence that FA oxidation is influenced by factors such as preceding diet, muscle glycogen content, exercise intensity, training status, training volume, and muscle fiber composition (14,51). A recent cross-sectional study of 300 subjects showed that a mere 12% of the variation in FA oxidation after 4-h fast could be explained by differences in training status, physical activity level, and sex, and it was concluded that differences in FA utilization between subjects remain largely unexplained (51).…”
mentioning
confidence: 99%
“…Tal fato justificaria uma possível diferença entre os sexos na recomendação de macronutrientes em esportes de longa duração. Contudo, outros autores não encontraram diferenças significativas, entre homens e mulheres, na proporção dos substratos utilizados durante o exercício [11][12][13][14][15][16][17][18][19] . Roepstorff et al 12 destacaram que a contribuição relativa de carboidratos e lipídeos como combustíveis, durante o exercício submáximo, é resultado da utilização dos diferentes carboidratos (glicose sangüínea e glicogênio muscular) e dos lipídeos (ácidos graxos de cadeia longa ligados à albumina plasmática, ácidos graxos dos triacilgliceróis presentes nas lipoproteínas de muito baixa densidade -VLDL-e ácidos graxos dos triacilgliceróis das células musculares).…”
Section: N T R O D U ç ã Ounclassified